(untitled) (Economics and region, 2023)
Analysis, evaluate and forecast the development of foreign economic relations between Ukraine and Japan. Studies of scientific problems related to the intensification of Ukrainian-Japanese cooperation in the foreign economic sphere were carried out using critical and scientific analysis, methods of scientific generalization and systematization, induction and deduction. To predict the volume of exports of domestic products to Japan, the following adaptive methods for forecasting: Holt model, Holt-Muir model were used. Since there are significant fluctuations in the series of dynamics (imports volume), we revealed abnormal values of the series. To detect anomalous values of the series, the Irwin method is used. The obtained results made it possible to draw a conclusion about the existing trends of further growth in the volume of export and import of industrial goods between Ukraine and Japan despite the conditions of the war. The analysis and forecast of exports to Japan indicate not only the aggressiveness of international marketing of Japanese entrepreneurs but also reflects the shortcomings of Ukrainian business - cannot or does not want to focus on the production and export of labor-intensive industrial products with higher value added. Despite the localization of active hostilities, Ukraine’s economic prospects remain extremely uncertain and depend on the duration of the war. In general, in order to support the export of traditional industrial goods (metal products. machinery and chemical products) to Japan, Ukraine needs to create an effective state policy of innovative development of domestic industry. The adaptive forecasting models presented in the article reproduce the dynamics of foreign trade relations between Ukraine and Japan. Unlike the existing ones, they are the most adequate forecasting tool in conditions of limited information and uncertainty. The results of the research presented in this work can be applied in practice for the analysis, evaluation and forecast of the development of foreign economic relations between the countries of the world.